Variable Performance of Lupus Anticoagulant Testing: The Australasian/Asia-Pacific Experience - Favaloro, Emmanuel J.; Dean, Elysse; Arunachalam, Sandya (Seminars in Thrombosis and Hemostasis, 2023)
Lupus anticoagulant (LA) is one of three tests identified as laboratory criteria for definite antiphospholipid syndrome (APS). The other two tests are anticardiolipin antibody (aCL) and anti-β2-glycoprotein I (aβ2GPI) antibody. The presence of LA is assessed using clot-based tests, while the presence of aCL and aβ2GPI is assessed by immunological assays. Since no test can be considered 100% sensitive or specific for LA, current guidelines recommend using two different clot-based assays reflecting different principles, with the dilute Russell viper venom time (dRVVT) and activated partial thromboplastin time (aPTT) recommended. Initially, LA-sensitive reagents are used to screen for LA, and then, in “screen-positive” samples, LA-“insensitive” reagents are used to confirm LA. Because LA assays are based on clot detection, anything that can interfere with fibrin clot development may affect test results. In particular, in addition to LA, the tests are also sensitive to the presence of a wide range of clinical anticoagulants, reflecting preanalytical issues for testing. We provide updated findings for LA testing in our geographic region, using recent data from the Royal College of Pathologists of Australasia Quality Assurance Programs, an international external quality assessment program with approximately 120 participants. Data show a wide variety of assays in use, especially for aPTT testing, and variable outcomes in reported numerical values with these assays when assessing proficiency samples. dRVVT testing mostly comprised reagents from three main manufacturing suppliers, which also showed differences in numerical values for the same homogeneous tested samples. Nevertheless, despite the use of different test reagents and processes, >98% of participants correctly identified LA-negative samples as LA-negative and LA-positive samples as LA positive. We hope our findings, reflecting on the heterogeneity of test processes and test data, help improve diagnostic testing for LA in the future.
Keywords: lupus anticoagulant; antiphospholipid antibodies; antiphospholipid syndrome; diagnosis; exclusion; laboratory testing; interpretation; external quality assessment; proficiency testing; random errors; test variability